The Effect of Profitability, Leverage and Liquidity on Firm Value in Coal Mining Companies Listed on the IDX for the Period 2018-2022 - Mudzakkir Farij; Laila Wardani (Socio-Economic and Humanistic Aspects for Township and Industry, 2024)
This study aims to examine the effect of profitability ratios, profitability ratios, and profitability ratios leverage and liquidity ratios to company value in coal mining companies listed on the Indonesia Stock Exchange for the period 2018-2022. The indicators used to measure profitability are Return on Assets (ROA), leverage using Debt to Equity Ratio (DER) and liquidity using Current Ratio (CR), while company value uses Tobin’s Q (Rasio Q). The type of research used is associative research with a quantitative approach. The population in this study were all coal mining companies listed on the Indonesia Stock Exchange with the sampling method, namely purposive sampling, Based on the criteria set, a total of 15 company samples were obtained. The data collection technique uses documentation techniques, while the data analysis method uses multiple linear regression analysis using the SPSS program. Based on the test and analysis of the research results, it shows that the profitability and leverage has a positive and significant effect on firm value, while liquidity has a positive and insignificant effect on firm value.